Correlation Between Local Chemical Composition and Formation of Different Types of Ordered Phases in the Polycrystalline Nickel‐Base Superalloy A718Plus. Issue 12 (28th July 2021) - Hausmann, Daniel; Förner, Andreas; Pröbstle, Martin; Hünert, Daniela; Felfer, Peter; Göken, Mathias; Neumeier, Steffen
Abstract : Allvac 718Plus is a derivative of alloy 718 for applications at higher temperatures in rotating and static components of gas turbines. According to literature, various phases as γ, γ′, η, δ, and γ″ can form with so far contradicting results. Herein, the precipitation behavior in different alloy conditions is investigated using transmission electron microscopy and atom probe tomography. The aim is to clarify how local variations in chemical composition alter the sequence of precipitation and type of precipitates that form. Material conditions with a minor volume fraction of η/δ phase and a high fraction of primary γ′ precipitates form γ″ phase due to excess of available Nb. Spherical γ′ precipitates with disc‐shaped γ″ precipitates at γ′ interfaces are observed. During discontinuous coarsening of η/δ plates mainly Nb is consumed which leads to an enrichment of γ′ forming elements and hence the heterogeneous nucleation of γ′ at the η/γ interface. The coexistence of thin η plates embedded in δ phase in grain boundary pinning precipitates could additionally be confirmed. These results show under which conditions certain primary phases form and how the resulting consumption and redistribution of phase promoting elements trigger the formation of other secondary phases. Abstract : The nickel‐base superalloy Allvac718 Plus is an advanced alloy for applications at higher temperatures and forms various precipitation phases. The correlation between local chemical composition and formation of different precipitate types is important to understand the precipitation behavior. Combining atom probe tomography and electron microscopy allow to clarify how the sequence of precipitation is altered.